The role of vitamin D3 in follicle development - Mingxia Li; Shuhui Hu; Jiaxiang Sun; Ying Zhang (BMC, 2024)
Abstract Vitamin D3 plays a crucial role in female reproduction. As research progresses, the mechanisms of action of vitamin D3 on follicular development have been widely discussed. Firstly, key enzymes involved in the synthesis and metabolism of vitamin D3 have been discovered in the ovary, suggesting that vitamin D3 can be synthesized and metabolized locally within the ovary. Additionally, the detection of vitamin D3 receptors (VDR) in follicles suggests that vitamin D3 may exert its effects by binding specifically to these receptors during follicular development. Further research indicates that vitamin D3 promotes follicular growth by enhancing the development of granulosa cells (GCs) and oocytes. Currently, the mechanism of action of vitamin D3 in follicular development is becoming increasingly clear. Vitamin D3 promotes oocyte development by regulating molecules involved in meiotic arrest in oocytes. It also enhances granulosa cell proliferation by stimulating steroid hormone synthesis and cell cycle regulation. Additionally, vitamin D3 exerts anti-inflammatory effects by reducing oxidative stress and advanced glycation end-products (AGEs), mitigating the detrimental effects of inflammation on follicular development. These functions of vitamin D3 have clinical applications, such as in treating polycystic ovary syndrome (PCOS), improving female fertility, and enhancing outcomes in in vitro fertilization (IVF). This review summarizes the research progress on the role and mechanisms of vitamin D3 in follicular development and briefly summarizes its clinical applications.